A self-crosslinking polymer and bottom anti-reflective coating composition and preparation method and application thereof
By using a self-crosslinking polymer as the bottom anti-reflective coating, the problem in the existing technology that the bottom anti-reflective coating cannot effectively fill defects on the substrate surface is solved, achieving better anti-reflective and hole-filling performance, and improving photolithography Image resolution for imaging.
Patent Information
- Application Number
- CN202311862460.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-29
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-12-29
AI Technical Summary
The existing bottom anti-reflective coating cannot effectively fill the base surface defects, resulting in unsatisfactory anti-reflective effect.
Use self -linked polymer as the bottom anti -reflex coating of the film formation resin, and the free radical polymerization reactions are introduced by introducing specific acrylic ethylene glycols, acrylic alcohols, and acrylic monosylodes. Packed and filling effects.
A better anti -reflector effect and filling performance are achieved, the exposure energy range and focal length are increased, and the impact of the base surface shape on the image resolution is reduced.
Smart Images

Figure CN117866135B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of semiconductor coating materials, and in particular relates to a self-crosslinking polymer and bottom anti-reflective coating composition, and a preparation method and application thereof. Background Art
[0002] Photoresist, commonly known as photoresist, is a photosensitive composition used to transfer images to a substrate. After a photoresist coating is formed on a substrate, the photoresist layer is divided into light radiation transparent and non-transparent areas through a photomask. The transparent area is exposed to an activating radiation source to undergo a chemical modification reaction, thereby transferring the pattern of the photomask to the photoresist coating, and finally forming an image on the substrate through development. During the exposure process, the light radiated to the photoresist coating may be reflected, causing spatial variations in the intensity of the actinic radiation, and the actinic radiation may also scatter toward unintended photoresist areas, causing changes in the line width or lack of uniformity of the pattern after development, which will have a significant impact on the image resolution.
[0003] At present, a bottom anti-reflection coating that can effectively eliminate the interference standing wave formed by light reflection is added between the photoresist and the substrate. The bottom anti-reflection coating can increase the exposure energy range and focal length, reduce the reflection of light, and reduce the circular notch caused by the scattering of reflected light to achieve the effect of improving image resolution. According to the material used, the bottom anti-reflection coating can be divided into an inorganic anti-reflection coating and an organic anti-reflection coating. The inorganic anti-reflection coating is made of materials such as titanium, titanium dioxide, titanium nitride, chromium oxide, carbon or amorphous silicon. The organic anti-reflection coating is made of polymer materials. Compared with the inorganic anti-reflection coating, the preparation of the organic anti-reflection coating does not require complex and expensive equipment, the polymer material does not diffuse from the organic anti-reflection coating to the photoresist layer during heating, coating and drying, and the organic anti-reflection coating has a higher light absorption rate and excellent etching rate.
[0004] However, there are certain structural defects on the surface of the substrate, and the introduction of the bottom anti-reflection coating cannot completely fill the defects, which will lead to the existence of gaps, and then cause the swing curve effect and the notch effect. The anti-reflection effect is not ideal and has great limitations. Summary of the invention
[0005] The first purpose of the present invention is to solve the problem that the existing bottom anti-reflection coating cannot be well filled into the surface defects of the substrate, resulting in unsatisfactory anti-reflection effect, and to obtain a new self-crosslinking polymer. The bottom anti-reflection coating with the self-crosslinking polymer as the film-forming resin has both excellent anti-reflection effect and hole-filling effect.
[0006] The second object of the present invention is to provide a method for preparing a self-crosslinking polymer.
[0007] The third object of the present invention is to provide a self-crosslinking polymer prepared by the above method.
[0008] A fourth object of the present invention is to provide a bottom anti-reflective coating composition.
[0009] A fifth object of the present invention is to provide application of the above self-crosslinking polymer and / or bottom anti-reflective coating composition in the semiconductor field.
[0010] Specifically, the self-crosslinking polymer provided by the present invention includes a structural unit 1 derived from an ethylene glycol acrylate monomer represented by formula (1);
[0011]
[0012] In formula (1), R 1 is a C1-C6 alkyl group, a C2-C6 ether alkyl group, a C2-C6 ketoalkyl group, an aldehyde group, a C2-C6 acyl group, a C2-C6 epoxy group, a C7-C12 aralkyl group, a C6-C12 alkaryl group or a C5-C8 cycloalkyl group; R 2 It is H or a C1-C6 alkyl group.
[0013] In some specific embodiments, the ethylene glycol acrylate monomer is selected from one or more compounds represented by formula (2) to formula (10);
[0014]
[0015] In some specific embodiments, the self-crosslinking polymer further comprises a structural unit 2 derived from an anthracene acrylate monomer of formula (11) and / or a structural unit 3 derived from an acrylic acid monoester monomer of formula (12);
[0016]
[0017] In formula (11), R 3 is an anthracene ring, R 4 is H or a C1-C6 alkyl group;
[0018] In formula (12), R 5 is a C1-C6 alkyl group, a C2-C6 ether alkyl group, a C2-C6 ketoalkyl group, an aldehyde group, a C2-C6 acyl group, a C2-C6 epoxy group, a C7-C12 aralkyl group, a C6-C12 alkaryl group or a C5-C8 cycloalkyl group; R 6 It is H or a C1-C6 alkyl group.
[0019] In some specific embodiments, the anthracene acrylate monomer is selected from one or more of 1-anthracene methyl methacrylate, 2-anthracene methyl methacrylate and 9-anthracene methyl methacrylate.
[0020] In some specific embodiments, the acrylic acid monoester monomer is selected from one or more of methyl methacrylate, methyl ethyl acrylate, ethyl methacrylate and 1-butoxyethyl methacrylate.
[0021] In some specific embodiments, the molar ratio of structural unit 1, structural unit 2 and structural unit 3 in the self-crosslinking polymer is 1:(0.05-20):(0.1-5).
[0022] The method for preparing the self-crosslinking polymer provided by the present invention comprises subjecting the ethylene glycol acrylate monomer represented by formula (1) and the optional anthracene acrylate monomer represented by formula (11) and / or the acrylic acid monoester monomer represented by formula (12) to a free radical polymerization reaction under the action of an initiator, thereby obtaining the self-crosslinking polymer;
[0023]
[0024] In formula (1), R 1 is a C1-C6 alkyl group, a C2-C6 ether alkyl group, a C2-C6 ketoalkyl group, an aldehyde group, a C2-C6 acyl group, a C2-C6 epoxy group, a C7-C12 aralkyl group, a C6-C12 alkaryl group or a C5-C8 cycloalkyl group; R 2 is H or a C1-C6 alkyl group;
[0025] In formula (11), R 3 is an anthracene ring, R 4 is H or a C1-C6 alkyl group;
[0026] In formula (12), R 5 is a C1-C6 alkyl group, a C2-C6 ether alkyl group, a C2-C6 ketoalkyl group, an aldehyde group, a C2-C6 acyl group, a C2-C6 epoxy group, a C7-C12 aralkyl group, a C6-C12 alkaryl group or a C5-C8 cycloalkyl group; R 6 It is H or a C1-C6 alkyl group.
[0027] In some specific embodiments, the initiator is an azo compound and / or a peroxide.
[0028] In some specific embodiments, the molar ratio of the ethylene glycol acrylate monomer to the initiator is 1:(0.01-0.1).
[0029] In some specific embodiments, the input molar ratio of the ethylene glycol acrylate monomer, the anthracene acrylate monomer and the acrylic acid monoester monomer is 1:(0.05-20):(0.1-5).
[0030] In some specific embodiments, the temperature of the free radical polymerization reaction is 60-100° C., and the time is 1-50 hours.
[0031] The present invention also provides a self-crosslinking polymer prepared by the method.
[0032] In some specific embodiments, the weight average molecular weight of the self-crosslinking polymer is 5000-7500, and the dispersion coefficient is 1.6-1.8.
[0033] The bottom anti-reflective coating composition provided by the present invention contains the self-crosslinking polymer described above.
[0034] In some specific embodiments, the bottom anti-reflective coating composition further contains an acid generator and / or an organic solvent.
[0035] In some specific embodiments, the acid generator is a photoacid generator and / or a thermal acid generator.
[0036] In some specific embodiments, the organic solvent is selected from one or more of methyl 2-hydroxyisobutyrate, cyclohexanone, cyclopentanone, butyrolactone, dimethylacetamide, dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, tetrahydrofurfuryl alcohol, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate and ethyl lactate.
[0037] In some specific embodiments, the content of the self-crosslinking polymer in the bottom anti-reflective coating composition is 0.5-20 wt %, the content of the acid generator is 0.01-10 wt %, and the content of the organic solvent is 70-99 wt %.
[0038] The present invention also provides the use of the self-crosslinking polymer and / or bottom anti-reflective coating composition in the semiconductor field.
[0039] Beneficial effects:
[0040] In the present invention, a self-crosslinking polymer having a diester structure is obtained by introducing a structural unit 1 derived from an ethylene glycol acrylate monomer shown in formula (1) and an optional structural unit 2 derived from an anthracene acrylate monomer shown in formula (11) and / or a structural unit 3 of an acrylic acid monoester monomer shown in formula (12). The self-crosslinking polymer has both excellent anti-reflection effect and hole-filling effect. When the self-crosslinking polymer is applied to photolithography imaging, it can increase the exposure energy range and focal length, reduce the influence of the substrate surface morphology on the uniformity of the key dimension, and reduce the circular notch caused by the scattering of reflected light, and alleviate the swing curve effect and concave notch effect caused by the different thickness of the photoresist caused by the substrate surface morphology, so as to finally achieve the effect of improving the image resolution. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is a SEM image of the silicon substrate surface provided in Example 1 of the present invention;
[0042] Figure 2 This is a SEM image of the silicon substrate surface provided in Example 2 of the present invention;
[0043] Figure 3 This is a SEM image of the silicon substrate surface provided in Example 3 of the present invention;
[0044] Figure 4 This is a SEM image of the silicon substrate surface provided in Example 4 of the present invention;
[0045] Figure 5 This is a SEM image of the silicon substrate surface provided in Example 5 of the present invention;
[0046] Figure 6 This is a SEM image of the silicon substrate surface provided for Comparative Example 1. DETAILED DESCRIPTION
[0047] The structure of the self-crosslinking polymer provided by the present invention comprises at least one structural unit derived from an ethylene glycol acrylate monomer represented by formula (1);
[0048]
[0049] In formula (1), R 1 is a C1-C6 alkyl group, a C2-C6 ether alkyl group, a C2-C6 ketoalkyl group, an aldehyde group, a C2-C6 acyl group, a C2-C6 epoxy group, a C6-C12 aralkyl group, a C6-C12 alkaryl group or a C5-C8 cycloalkyl group; R 2 is H or a C1-C6 alkyl group. Specific examples of C1-C6 alkyl groups include, but are not limited to: -CH 3 、-CH 2 CH 3 、-CH 2 (CH 3 )CH 2 CH 3 or -(CH 2 ) 5 CH 3 Specific examples of C2-C6 ether alkyl groups include, but are not limited to: -CH 2 OCH 3 、-CH 2 CH 2 OCH 2 CH 3 、-CH 2 (CH 3 )CH 2 OCH 3 or -C(CH3 ) 2 CH 2 OCH 3 Specific examples of C2-C6 ketoalkyl groups include, but are not limited to: -CH 2 CHO, -CH 2 COCH 3 、-CH 2 CH 2 COCH 3 or -CH 2 (CH 3 )CH 2 COCH 3 Specific examples of C2 to C6 acyl groups include, but are not limited to: -COCH 3 、-COCH 2 CH 3 、-COCH 2 CH 2 CH 3 or -COCH(CH 3 )CH 2 CH 3 Specific examples of C2-C6 epoxy groups include, but are not limited to: -[-CH(O)CH 2 -]、-CH 2 [-CH(O)CH 2 -]、-CH 2 CH 2 [-CH(O)CH 2 -] or -CH 2 CH 2 [-CH(O)CH-]CH 3 The C7-C12 aralkyl groups include but are not limited to: -CH 2 Ph, -CH 2 CH 2 Ph, -CH 2 CH 2 CH 2 Ph or -CH 2 CH(CH 3 )CH 2 Ph. Specific examples of C6-C12 alkylaryl groups include, but are not limited to: -Ph, -Ph-CH 3 ,-PhCH 2 CH 3 ,-PhCH 2 CH 2 CH 3 、-PhCH(CH 3 )CH 3 or -PhCH 2 CH(CH 3)CH 3 Specific examples of C5-C8 cycloalkyl groups include, but are not limited to, cyclopentyl and cyclohexyl.
[0050] The structure of the self-crosslinking polymer provided by the present invention may also include a structural unit 2 derived from an anthracene acrylate monomer of formula (11) and / or a structural unit 3 derived from an acrylic acid monoester monomer of formula (12);
[0051]
[0052] In formula (11), R 3 is an anthracene ring, R 4 is H or a C1-C6 alkyl group;
[0053] In formula (12), R 5 is a C1-C6 alkyl group, a C2-C6 ether alkyl group, a C2-C6 ketoalkyl group, an aldehyde group, a C2-C6 acyl group, a C2-C6 epoxy group, a C7-C12 aralkyl group, a C6-C12 alkaryl group or a C5-C8 cycloalkyl group; R 6 is H or a C1-C6 alkyl group. Specific examples of C1-C6 alkyl groups include, but are not limited to: -CH 3 、-CH 2 CH 3 、-CH 2 (CH 3 )CH 2 CH 3 or -(CH 2 ) 5 CH 3 Specific examples of C2-C6 ether alkyl groups include, but are not limited to: -CH 2 OCH 3 、-CH 2 CH 2 OCH 2 CH 3 、-CH 2 (CH 3 )CH 2 OCH 3 or -C(CH 3 ) 2 CH 2 OCH 3 Specific examples of C2-C6 ketoalkyl groups include, but are not limited to: -CH 2 CHO, -CH 2 COCH 3 、-CH 2 CH 2 COCH 3 or -CH 2 (CH 3)CH 2 COCH 3 Specific examples of C2 to C6 acyl groups include, but are not limited to: -COCH 3 、-COCH 2 CH 3 、-COCH 2 CH 2 CH 3 or -COCH(CH 3 )CH 2 CH 3 Specific examples of C2-C6 epoxy groups include, but are not limited to: -[-CH(O)CH 2 -]、-CH 2 [-CH(O)CH 2 -]、-CH 2 CH 2 [-CH(O)CH 2 -] or -CH 2 CH 2 [-CH(O)CH-]CH 3 The C7-C12 aralkyl groups include but are not limited to: -CH 2 Ph, -CH 2 CH 2 Ph, -CH 2 CH 2 CH 2 Ph or -CH 2 CH(CH 3 )CH 2 Ph. Specific examples of C6-C12 alkylaryl groups include, but are not limited to: -Ph, -Ph-CH 3 ,-PhCH 2 CH 3 ,-PhCH 2 CH 2 CH 3 、-PhCH(CH 3 )CH 3 or -PhCH 2 CH(CH 3 )CH 3 Specific examples of C5-C8 cycloalkyl groups include, but are not limited to, cyclopentyl and cyclohexyl.
[0054] The present invention has no particular limitation on the ratio of structural unit one, structural unit two and structural unit three in the self-crosslinking polymer structure, that is, the structural unit one, structural unit two and structural unit three in the self-crosslinking polymer structure provided in the present invention can exist in any ratio. In some specific embodiments, the ratio of structural unit one, structural unit two and structural unit three in the self-crosslinking polymer is preferably 1: (0.05-20): (0.1-5), such as 1: 0.05: 0.1, 1: 0.5: 0.1, 1: 1: 1, 1: 5: 1, 1: 15: 1.2, 1: 17.36: 1.6, 1: 20: 5 or any value therebetween. More preferably, the ratio of structural unit one, structural unit two and structural unit three in the self-crosslinking polymer is 1: (15-20): (1-2), at which point the self-crosslinking polymer achieves ideal anti-reflection performance and hole filling performance.
[0055] The present invention has no particular limitation on the distribution of the structural unit 1, structural unit 2 and structural unit 3 in the self-crosslinking polymer structure, that is, the structural unit 1, structural unit 2 and structural unit 3 in the self-crosslinking polymer structure provided in the present invention can be distributed in any manner, and can be random copolymerization, alternating copolymerization, block copolymerization or graft copolymerization, preferably random copolymerization. Among them, the "one", "two" and "three" in the structural unit 1, structural unit 2 and structural unit 3 are only for the purpose of distinction for the convenience of description, and have no other special meaning.
[0056] In some specific embodiments, specific examples of the ethylene glycol acrylate monomer include, but are not limited to, one or more of the compounds represented by formula (2) to formula (10):
[0057]
[0058] In some specific embodiments, specific examples of the anthracene acrylate monomer include, but are not limited to, one or more of 1-anthracene methyl methacrylate, 2-anthracene methyl methacrylate, and 9-anthracene methyl methacrylate.
[0059] In some specific embodiments, specific examples of the acrylic acid monoester monomer include, but are not limited to, one or more of methyl methacrylate, methyl ethyl acrylate, ethyl methacrylate and 1-butoxyethyl methacrylate.
[0060] The preparation method of the self-crosslinking polymer provided by the present invention specifically comprises: subjecting the ethylene glycol acrylate monomer represented by formula (1) and the optional anthracene acrylate monomer represented by formula (11) and / or the acrylic acid monoester monomer represented by formula (12) to a free radical polymerization reaction under the action of an initiator to obtain the self-crosslinking polymer.
[0061] In the preparation process of the self-crosslinking polymer, the initiator can be any existing substance capable of initiating free radical polymerization, and specific examples include but are not limited to azo compounds and / or peroxides. In some specific embodiments, the initiator is preferably an azo compound, and specific examples of the azo compound include but are not limited to: one or more of azobisisobutyronitrile, azobisisoheptanenitrile and 2,2'-azobis(isobutyric acid) dimethyl ester.
[0062] In the preparation process of the self-crosslinking polymer, the molar ratio of the ethylene glycol acrylate monomer to the initiator is preferably 1:(0.01-0.1), such as 1:0.01, 1:0.03, 1:0.05, 1:0.07, 1:0.08, 1:0.1 or any value therebetween.
[0063] In the preparation process of the self-crosslinking polymer, the input molar ratio of the ethylene glycol acrylate monomer, the anthracene acrylate monomer and the acrylate monoester monomer is preferably 1:(0.05-20):(0.1-5), such as 1:0.05:0.1, 1:0.5:0.1, 1:1:1, 1:5:1, 1:15:1.2, 1:17.36:1.6, 1:20:5 or any value therebetween. More preferably, in the preparation process of the self-crosslinking polymer, the input molar ratio of the ethylene glycol acrylate monomer, the anthracene acrylate monomer and the anthracene acrylate monomer is 1:(15-20):(1-2), at which point the obtained self-crosslinking polymer can achieve more ideal anti-reflection performance and hole filling performance.
[0064] In the preparation process of the self-crosslinking polymer, specific examples of the solvent used in the free radical polymerization reaction include, but are not limited to, one or more of benzene, toluene, xylene, ethyl lactate, butyl lactate, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, and N-methylpyrrolidone. In some more preferred embodiments, the solvent is selected from one or more of ethyl lactate, butyl lactate, propylene glycol monomethyl ether, and propylene glycol monomethyl ether acetate.
[0065] In the preparation process of the self-crosslinking polymer, the conditions of the free radical polymerization reaction specifically include: the temperature is preferably 60-100°C, such as 60°C, 63°C, 65°C, 70°C, 80°C, 85°C, 90°C, 95°C, 100°C or any value therebetween, more preferably 70-90°C; the time is preferably 1-50h, such as 1h, 2.5h, 5h, 8h, 10h, 12h, 18h, 20h, 25h, 30h, 40h, 50h or any value therebetween, more preferably 5-20h.
[0066] The present invention also provides a self-crosslinking polymer prepared by the above method. The weight average molecular weight of the self-crosslinking polymer is preferably 5000-7500, such as 5000, 5120, 5200, 5400, 5800, 6000, 6300, 6500, 6800, 7000, 7250, 7500 or any value therebetween; the dispersion coefficient is preferably 1.6-1.8, such as 1.6, 1.63, 1.7, 1.72, 1.75, 1.8 or any value therebetween.
[0067] The bottom anti-reflective coating composition provided by the present invention comprises at least the self-crosslinking polymer described above, and may further comprise an acid generator and / or an organic solvent. Wherein, the content of the self-crosslinking polymer in the bottom anti-reflective coating composition is preferably 0.5-20wt%, such as 0.5wt%, 0.7wt%, 1wt%, 2wt%, 5wt%, 10wt%, 12wt%, 15wt%, 20wt% or any value therebetween, more preferably 2-4wt%; the content of the acid generator is preferably 0.01-10wt%, such as 0.01wt%, 0.02wt%, 0.05wt%, 0.1wt%, 0.5wt%, 1wt%, 3wt%, 5wt%, 8wt%, 10wt% or any value therebetween, more preferably 0.03-0.15wt%; the content of the organic solvent is preferably 70-99wt%, such as 70wt%, 75wt%, 78wt%, 80wt%, 85wt%, 90wt%, 95wt%, 99wt% or any value therebetween, more preferably 75-85wt%.
[0068] In the present invention, the acid generator is capable of decomposing and generating H under certain conditions. + Specific examples include, but are not limited to, photoacid generators and / or thermal acid generators.
[0069] In some specific embodiments, the acid generator is preferably a photoacid generator, and specific examples of the photoacid generator include, but are not limited to, one or more of sulfonium salt compounds, iodonium salt compounds, and organic sulfonic acids. In some preferred embodiments, the photoacid generator is selected from dodecylbenzenesulfonic acid, p-toluenesulfonic acid, phthalimide trifluoromethanesulfonate / salt, dinitrobenzyl toluenesulfonate / salt, n-decyl disulfone, naphthyl imide trifluoromethanesulfonate / salt, diphenyliodonium trifluoromethanesulfonate, diphenyliodonium perfluorobutylsulfonate, diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroarsenate, diphenyliodonium hexafluoroantimonate, diphenyl-p-methoxyphenylsulfonium trifluoromethanesulfonate, diphenyl-p-toluenesulfonium trifluoromethanesulfonate, diphenyl-p-tert-butylphenylsulfonium trifluoromethanesulfonic acid The invention can be selected from the group consisting of diphenylsulfonium trifluoromethanesulfonate, diphenylsulfonium trifluoromethanesulfonate, triphenylsulfonium trifluoromethanesulfonate, tri(p-tert-butylphenyl)sulfonium trifluoromethanesulfonate, diphenylsulfonium perfluorobutylsulfonate, diphenylsulfonium perfluorobutylsulfonate, diphenylsulfonium perfluorobutylsulfonate, diphenylsulfonium perfluorobutylsulfonate, triphenylsulfonium perfluorobutylsulfonate, tri(p-tert-butylphenyl)sulfonium trifluoromethanesulfonate, hexafluoroarsenate / salt, triphenylsulfonium hexafluoroantimonate and dibutylnaphthylsulfonium trifluoromethanesulfonate.
[0070] The present invention also provides the use of the self-crosslinking polymer and / or bottom anti-reflection coating in the semiconductor field.
[0071] In the practical application of the self-crosslinking polymer and / or the bottom anti-reflection coating, the self-crosslinking polymer and / or the bottom anti-reflection coating can be coated on the substrate by spin coating, spray coating, etc. Wherein, the substrate is commonly used in semiconductors, and specific examples thereof include but are not limited to: one or more of a silicon substrate, a silicon dioxide substrate, an aluminum-aluminum oxide microelectronic wafer, a gallium arsenide substrate, a silicon carbide substrate, a ceramic substrate, a quartz substrate, a glass substrate, a copper substrate, or an indium tin oxide substrate.
[0072] In practical applications of the self-crosslinking polymer and / or the bottom anti-reflective coating, the temperature at which the self-crosslinking polymer and / or the bottom anti-reflective coating are cured is such that the self-crosslinking polymer and the bottom anti-reflective coating are substantially insoluble in the photoresist solvent and the developer solution used; the curing temperature may be exemplarily 90 to 240° C., such as 90° C., 95° C., 100° C., 120° C., 150° C., 200° C., 220° C., 240° C. or any value therebetween; preferably 150 to 210° C.
[0073] Embodiments of the present invention are described in detail below, and the examples of the embodiments are intended to be used to explain the present invention, but should not be construed as limiting the present invention. In the embodiments, if specific techniques or conditions are not specified, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not specified for reagents or instruments used, they are all conventional products that can be obtained commercially.
[0074] The silicon substrates used in the following embodiments and comparative examples have the same specifications.
[0075] Preparation Example 1
[0076] This preparation example is used to illustrate the preparation of the self-crosslinking polymer provided by the present invention, and specifically includes:
[0077] In a 100mL three-necked flask, add 49.00g of propylene glycol monomethyl ether acetate, 1.56g of ethylene glycol acetoacetate (7.3mmol), 4.62g of 1-butoxyethyl methacrylate (24.8mmol), 4.14g of glycidyl methacrylate (29.1mmol), 7.30g of methyl methacrylate (72.9mmol) and 3.22g of 9-anthracenemethyl methacrylate (11.7mmol), and stir for 30min under nitrogen flow until completely dissolved. Then, heat to 80°C, add 1.0g of 2,2'-azobis(isobutyric acid) dimethyl ester to the above solution, and stir for 8h at 80°C under nitrogen atmosphere to obtain a self-crosslinking polymer solution.
[0078] After testing, the obtained self-crosslinking polymer solution contains a copolymer of ethylene glycol methacrylate, 1-butoxyethyl methacrylate, glycidyl methacrylate, methyl methacrylate and 9-anthracenemethyl methacrylate, and the concentration of the self-crosslinking polymer in the self-crosslinking polymer solution is 30.27wt%, the weight average molecular weight is 6650, and the dispersion coefficient is 1.70.
[0079] Preparation Example 2
[0080] This preparation example is used to illustrate the preparation of the self-crosslinking polymer provided by the present invention, and specifically includes:
[0081] In a 100 mL three-necked flask, 49.00 g of propylene glycol monomethyl ether acetate, 1.45 g of 1-butyric acid ethylene glycol methacrylate (7.3 mmol), 4.62 g of 1-butoxyethyl methacrylate (24.8 mmol), 4.14 g of glycidyl methacrylate (29.1 mmol), 7.30 g of methyl methacrylate (72.9 mmol) and 3.22 g of 9-anthracenemethyl methacrylate (11.7 mmol) were added, and stirred for 30 min under circulating nitrogen until completely dissolved; then the temperature was raised to 80° C., 1.0 g of 2,2'-azobis(isobutyric acid)dimethyl ester was added to the above solution, and stirred at 80° C. under nitrogen atmosphere for 8 h to obtain a self-crosslinking polymer solution.
[0082] After testing, the obtained self-crosslinking polymer solution contains a copolymer of 1-butyric acid ethylene glycol methacrylate, 1-butoxyethyl methacrylate, glycidyl methacrylate, methyl methacrylate and 9-anthracenemethyl methacrylate, and the concentration of the self-crosslinking polymer in the self-crosslinking polymer solution is 30.19wt%, the weight average molecular weight is 6610, and the dispersion coefficient is 1.71.
[0083] Preparation Example 3
[0084] This preparation example is used to illustrate the preparation of the self-crosslinking polymer provided by the present invention, and specifically includes:
[0085] In a 100 mL three-necked flask, add 49.00 g of propylene glycol monomethyl ether acetate, 1.71 g of 2-(benzoyloxy)ethyl methacrylate (7.3 mmol), 4.62 g of 1-butoxyethyl methacrylate (24.8 mmol), 4.14 g of glycidyl methacrylate (29.1 mmol), 7.30 g of methyl methacrylate (72.9 mmol) and 3.22 g of 9-anthracenemethyl methacrylate (11.7 mmol), and stir for 30 min under nitrogen flow until completely dissolved. Then, heat to 80°C, add 1.0 g of 2,2'-azobis(isobutyric acid) dimethyl ester to the above solution, and stir for 8 h at 80°C under nitrogen atmosphere to obtain a self-crosslinking polymer solution.
[0086] After testing, the obtained self-crosslinking polymer solution contains a copolymer of 1-benzoyl methacrylate, 1-butoxyethyl methacrylate, glycidyl methacrylate, methyl methacrylate and 9-anthracenemethyl methacrylate, and the concentration of the self-crosslinking polymer in the self-crosslinking polymer solution is 30.33wt%, the weight average molecular weight is 6705, and the dispersion coefficient is 1.72.
[0087] Preparation Example 4
[0088] This preparation example is used to illustrate the preparation of the self-crosslinking polymer provided by the present invention, and specifically includes:
[0089] In a 100 mL three-necked flask, add 49.00 g of propylene glycol monomethyl ether acetate, 1.76 g of 1-acetyl butyric acid ethylene glycol methacrylate (7.3 mmol), 4.62 g of 1-butoxyethyl methacrylate (24.8 mmol), 4.14 g of glycidyl methacrylate (29.1 mmol), 7.30 g of methyl methacrylate (72.9 mmol) and 3.22 g of 9-anthracenemethyl methacrylate (11.7 mmol), and stir for 30 min under nitrogen flow until completely dissolved. Then, heat to 80 ° C, add 1.0 g of 2,2'-azobis(isobutyric acid) dimethyl ester to the above solution, and stir for 8 h at 80 ° C under nitrogen atmosphere to obtain a self-crosslinking polymer solution.
[0090] The structure of 1-acetylbutyric acid ethylene glycol methacrylate is as follows:
[0091]
[0092] After testing, the obtained self-crosslinking polymer solution contains a copolymer of 1-acetylbutyric acid ethylene glycol methacrylate, 1-butoxyethyl methacrylate, glycidyl methacrylate, methyl methacrylate and 9-anthracenemethyl methacrylate, and the concentration of the self-crosslinking polymer in the self-crosslinking polymer solution is 30.39wt%, the weight average molecular weight is 6680, and the dispersion coefficient is 1.71.
[0093] Preparation Example 5
[0094] This preparation example is used to illustrate the preparation of the self-crosslinking polymer provided by the present invention, and specifically includes:
[0095] In a 100mL three-necked flask, add 49.00g of propylene glycol monomethyl ether acetate, 3.21g of ethylene glycol acetoacetate (15mmol), 4.62g of 1-butoxyethyl methacrylate (24.8mmol), 4.14g of glycidyl methacrylate (29.1mmol), 6.53g of methyl methacrylate (65.2mmol) and 3.22g of 9-anthracenemethyl methacrylate (11.7mmol), and stir for 30min under nitrogen flow until completely dissolved. Then, heat to 80°C, add 1.0g of 2,2'-azobis(isobutyric acid) dimethyl ester to the above solution, and stir for 8h at 80°C under nitrogen atmosphere to obtain a self-crosslinking polymer solution.
[0096] After testing, the obtained self-crosslinking polymer solution contains a copolymer of ethylene glycol methacrylate, 1-butoxyethyl methacrylate, glycidyl methacrylate, methyl methacrylate and 9-anthracenemethyl methacrylate, and the concentration of the self-crosslinking polymer in the self-crosslinking polymer solution is 31.60wt%, the weight average molecular weight is 6843, and the dispersion coefficient is 1.73.
[0097] Comparative Preparation Example 1
[0098] This comparative preparation example is used to illustrate the preparation of a reference self-crosslinking polymer, which specifically includes:
[0099] In a 100mL three-necked flask, add 49.00g of propylene glycol monomethyl ether acetate, 4.62g of 1-butoxyethyl methacrylate (24.8mmol), 4.14g of glycidyl methacrylate (29.1mmol), 8.02g of methyl methacrylate (80.2mmol) and 3.22g of 9-anthracenemethyl methacrylate (11.7mmol), and stir for 30min under nitrogen flow until completely dissolved. Then heat to 80°C, add 1.0g of 2,2'-azobis(isobutyric acid) dimethyl ester to the above solution, and stir for 8h at 80°C under nitrogen atmosphere to obtain a self-crosslinking polymer solution.
[0100] After testing, the obtained self-crosslinking polymer solution contains a copolymer of 1-butoxyethyl methacrylate, glycidyl methacrylate, methyl methacrylate and 9-anthracenemethyl methacrylate, and the concentration of the self-crosslinking polymer in the self-crosslinking polymer solution is 29.99wt%, the weight average molecular weight is 6562, and the dispersion coefficient is 1.72.
[0101] Example 1
[0102] This example is used to illustrate the bottom anti-reflection coating composition provided by the present invention. The preparation of the composition comprises: adding 60.39 g of propylene glycol monomethyl ether acetate and 29.04 g of ethyl lactate to 10.57 g of the self-crosslinking polymer solution provided in Preparation Example 1 (containing 3.2 g of the self-crosslinking polymer) and mixing them evenly, and then filtering through a polyethylene microfilter with a pore size of 0.01 μm to obtain the bottom anti-reflection coating composition.
[0103] The obtained bottom anti-reflection coating composition was spin-coated on the etched silicon substrate at 1999 rpm for 60 seconds, and the silicon substrate coated with the bottom anti-reflection coating composition was baked at 220° C. for 60 seconds to form a bottom anti-reflection coating with a thickness of 60 nm on the silicon substrate.
[0104] Example 2
[0105] In this example, a bottom anti-reflective coating composition was prepared according to the method provided in Example 1, except that 10.60 g of the self-crosslinking polymer solution provided in Preparation Example 2 (containing 3.2 g of the self-crosslinking polymer) was used instead of 10.57 g of the self-crosslinking polymer solution provided in Preparation Example 1, and other conditions were the same to obtain a bottom anti-reflective coating composition.
[0106] The obtained bottom anti-reflection coating composition was spin-coated on the etched silicon substrate at 1999 rpm for 60 seconds, and the silicon substrate coated with the bottom anti-reflection coating composition was baked at 220° C. for 60 seconds to form a bottom anti-reflection coating with a thickness of 60 nm on the silicon substrate.
[0107] Example 3
[0108] In this example, a bottom anti-reflective coating composition was prepared according to the method provided in Example 1, except that 10.55 g of the self-crosslinking polymer solution provided in Preparation Example 3 (containing 3.2 g of the self-crosslinking polymer) was used instead of 10.57 g of the self-crosslinking polymer solution provided in Preparation Example 1, and other conditions were the same to obtain a bottom anti-reflective coating composition.
[0109] The obtained bottom anti-reflection coating composition was spin-coated on the etched silicon substrate at 1999 rpm for 60 seconds, and the silicon substrate coated with the bottom anti-reflection coating composition was baked at 220° C. for 60 seconds to form a bottom anti-reflection coating with a thickness of 60 nm on the silicon substrate.
[0110] Example 4
[0111] In this example, a bottom anti-reflective coating composition was prepared according to the method provided in Example 1, except that 10.53 g of the self-crosslinking polymer solution provided in Preparation Example 4 (containing 3.2 g of the self-crosslinking polymer) was used instead of 10.57 g of the self-crosslinking polymer solution provided in Preparation Example 1, and other conditions were the same to obtain a bottom anti-reflective coating composition.
[0112] The obtained bottom anti-reflection coating composition was spin-coated on the etched silicon substrate at 1999 rpm for 60 seconds, and the silicon substrate coated with the bottom anti-reflection coating composition was baked at 220° C. for 60 seconds to form a bottom anti-reflection coating with a thickness of 60 nm on the silicon substrate.
[0113] Example 5
[0114] In this example, a bottom anti-reflective coating composition was prepared according to the method provided in Example 1, except that 10.12 g of the self-crosslinking polymer solution provided in Preparation Example 5 (containing 3.2 g of the self-crosslinking polymer) was used instead of 10.57 g of the self-crosslinking polymer solution provided in Preparation Example 1. Other conditions were the same to obtain a bottom anti-reflective coating composition.
[0115] The obtained bottom anti-reflection coating composition was spin-coated on the etched silicon substrate at 1999 rpm for 60 seconds, and the silicon substrate coated with the bottom anti-reflection coating composition was baked at 220° C. for 60 seconds to form a bottom anti-reflection coating with a thickness of 60 nm on the silicon substrate.
[0116] Comparative Example 1
[0117] This comparative example prepared a bottom anti-reflective coating composition according to the method provided in Example 1, except that 10.67 g of the self-crosslinking polymer solution provided in Comparative Preparation Example 1 (containing 3.2 g of the self-crosslinking polymer) was used instead of 10.57 g of the self-crosslinking polymer solution provided in Preparation Example 1, and other conditions were the same to obtain a bottom anti-reflective coating composition.
[0118] The obtained bottom anti-reflection coating composition was spin-coated on the etched silicon substrate at 1999 rpm for 60 seconds, and the silicon substrate coated with the bottom anti-reflection coating composition was baked at 220° C. for 60 seconds to form a bottom anti-reflection coating with a thickness of 60 nm on the silicon substrate.
[0119] Test Case
[0120] The bottom anti-reflection coatings of the above examples and comparative examples were subjected to performance tests according to the following methods.
[0121] (1) Refractive index n: The anti-reflection coating was tested using an ellipsometer (purchased from Woollman). The test results are shown in Table 1.
[0122] (2) Absorbance k: The anti-reflection coating was tested using an etching device TE-8500P (purchased from TEL). The test results are shown in Table 1.
[0123] (3) Etching rate: The anti-reflective coating was tested using TE-8500P (purchased from TEL). The test results are shown in Table 1.
[0124] (4) Hole filling performance: The silicon substrates of the samples obtained in the above embodiments and comparative examples were tested using a scanning electron microscope. The results obtained in Examples 1 to 5 and Comparative Example 1 are shown in Table 1. Figure 1 to Figure 6 .from Figure 1 to Figure 6It can be seen that the bottom anti-reflective coating composition provided by the present invention can be well filled into the surface defects of the silicon substrate surface and has good hole-filling performance, while the bottom anti-reflective coating composition obtained in Comparative Example 1 cannot be well filled into the surface defects of the silicon substrate and has poor hole-filling performance.
[0125] Table 1 Anti-reflection performance
[0126]
[0127] It can be seen from the test results that, compared with the comparative example, the anti-reflective coating composition provided by the embodiment of the present invention has good anti-reflective performance.
[0128] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.
Claims
1. A self-crosslinking polymer, characterized in that The self-crosslinking polymer comprises a structural unit 1 derived from an ethylene glycol acrylate monomer represented by formula (1); In formula (1), R1 is a C1-C6 alkyl group, a C2-C6 ether alkyl group, a C2-C6 ketoalkyl group, an aldehyde group, a C2-C6 acyl group, a C2-C6 epoxy group, a C7-C12 aralkyl group, a C6-C12 alkaryl group or a C5-C8 cycloalkyl group; R2 is H or a C1-C6 alkyl group; The self-crosslinking polymer further comprises a structural unit 2 derived from an anthracene acrylate monomer of formula (11) and a structural unit 3 derived from an acrylic acid monoester monomer of formula (12); In formula (11), R3 is an anthracene ring, and R4 is H or a C1-C6 alkyl group; In formula (12), R5 is a C1~C6 alkyl group, a C2~C6 ether alkyl group, a C2~C6 ketoalkyl group, an aldehyde group, a C2~C6 acyl group, a C2~C6 epoxy group, a C7~C12 aralkyl group, a C6~C12 alkylaryl group or a C5~C8 cycloalkyl group; R6 is H or a C1~C6 alkyl group.
2. The self-crosslinking polymer according to claim 1, characterized in that The ethylene glycol acrylate monomer is selected from one or more compounds represented by formula (2) to formula (10); 3. The self-crosslinking polymer according to claim 1, characterized in that The anthracene acrylate monomer is selected from one or more of 1-anthracene methyl methacrylate, 2-anthracene methyl methacrylate and 9-anthracene methyl methacrylate.
4. The self-crosslinking polymer according to claim 1, characterized in that The acrylic acid monoester monomer is selected from one or more of methyl methacrylate, methyl ethyl acrylate, ethyl methacrylate and 1-butoxyethyl methacrylate.
5. The self-crosslinking polymer according to claim 1, characterized in that The molar ratio of the structural unit 1, the structural unit 2 and the structural unit 3 in the self-crosslinking polymer is 1:(0.05-20):(0.1-5).
6. A method for preparing a self-crosslinking polymer, characterized in that: The method comprises: subjecting an ethylene glycol acrylate monomer represented by formula (1), an anthracene acrylate monomer represented by formula (11) and an acrylic acid monoester monomer represented by formula (12) to a free radical polymerization reaction under the action of an initiator to obtain the self-crosslinking polymer; Formula (1); Formula (11), Formula (12); In formula (1), R1 is a C1-C6 alkyl group, a C2-C6 ether alkyl group, a C2-C6 ketoalkyl group, an aldehyde group, a C2-C6 acyl group, a C2-C6 epoxy group, a C6-C12 aralkyl group, a C6-C12 alkaryl group or a C5-C8 cycloalkyl group; R2 is H or a C1-C6 alkyl group; In formula (11), R3 is an anthracene ring, and R4 is H or a C1-C6 alkyl group; In formula (12), R5 is a C1~C6 alkyl group, a C2~C6 ether alkyl group, a C2~C6 ketoalkyl group, an aldehyde group, a C2~C6 acyl group, a C2~C6 epoxy group, a C7~C12 aralkyl group, a C6~C12 alkylaryl group or a C5~C8 cycloalkyl group; R6 is H or a C1~C6 alkyl group.
7. The method for preparing a self-crosslinking polymer according to claim 6, characterized in that: The initiator is an azo compound and / or a peroxide.
8. The method for preparing a self-crosslinking polymer according to claim 6, characterized in that: The input molar ratio of the ethylene glycol acrylate monomer to the initiator is 1:(0.01-0.1).
9. The method for preparing a self-crosslinking polymer according to claim 6, characterized in that: The input molar ratio of the ethylene glycol acrylate monomer, the anthracene alcohol acrylate monomer and the monoacrylate monomer is 1:(0.05-20):(0.1-5).
10. The method for preparing a self-crosslinking polymer according to claim 6, characterized in that: The temperature of the free radical polymerization reaction is 60-100° C. and the time is 1-50 hours.
11. A self-crosslinking polymer obtained by the method for preparing a self-crosslinking polymer according to any one of claims 6 to 10.
12. A bottom anti-reflective coating composition, characterized in that: The bottom anti-reflective coating composition contains the self-crosslinking polymer according to any one of claims 1 to 5 and 11.
13. The bottom anti-reflective coating composition according to claim 12, characterized in that The bottom anti-reflective coating composition further contains an acid generator and / or an organic solvent.
14. The bottom anti-reflective coating composition according to claim 13, characterized in that The acid generator is a photoacid generator and / or a thermal acid generator.
15. The bottom anti-reflective coating composition according to claim 13, characterized in that The organic solvent is selected from one or more of methyl 2-hydroxyisobutyrate, cyclohexanone, cyclopentanone, butyrolactone, dimethylacetamide, dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, tetrahydrofurfuryl alcohol, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate and ethyl lactate.
16. The bottom anti-reflective coating composition according to claim 13, characterized in that The bottom anti-reflective coating composition comprises 0.5-20 wt % of the self-crosslinking polymer, 0.01-10 wt % of the acid generator, and 70-99 wt % of the organic solvent.
17. Use of the self-crosslinking polymer according to any one of claims 1 to 5 and 11 and / or the bottom anti-reflective coating composition according to any one of claims 12 to 16 in the semiconductor field.
Citation Information
Patent Citations
Process for producing an image using a first minimum bottom antireflective coating composition
CN101034259A
Organic polymer with anti-reflective coating layer and its preparing method
CN1301797A